Pengaruh Komunikasi, Kepemimpinan dan Lingkungan Kerja Terhadap Stres Kerja Pegawai pada PD. Pasar Kota Singaraja Unit Pasar Anyar - indra, dewa; Utama, I Wayan Mudiartha (E-Jurnal Manajemen; Vol 3 No 1 (2014), 2014)
This research was conducted with the aim to determine the significant influence of variables simultaneously and partial communication, leadership and work environment on employee stress in PD. Pasar Kota Singaraja Unit Pasar Anyar. The research was conducted in PD. Pasar Kota Singaraja Unit Pasar Anyar located at Jalan Recent Diponegoro. Sampel used as many as 45 people. Multiple regression is used to solve the problem of this research. Communication, leadership and work environment simultaneously significant effect on employee stress in PD. Pasar Kota Singaraja Unit Pasar Anyar with calculated F value = 118.594 sig = 0.00. Communication, leadership and work environment partially significant effect on employee stress in PD. Pasar Kota Singaraja Unit Pasar Anyar with t value respectively communication variables = 4.712, = 7.753 variable leadership, work environment variables = 7.359. Keywords: communication, leadership, work environment, employee stress